2014
DOI: 10.2174/13862073113166660066
|View full text |Cite
|
Sign up to set email alerts
|

An In Silico Appraisal of Azoic and Disulphide Derivatives for Anticancer Activity Against HPV E6 Oncoprotein to Medicate Cervical Cancer

Abstract: Cervical cancer is the second largest form of cancer to infest the leading cause of death in women worldwide. There are many causes of cancer but viruses are the most common among them. Human papillomaviruses (HPVs) are found to be the causative organism in almost 99.7% of the cases. HPV16 is the most frequent HPV type in malignant neoplastic growth in about 60% of cervical carcinoma cases. There is limited success achieved in surgical removal or by immune modulation and more effective therapies are under inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The FlexX docking algorithm as implemented in LeadIT executed the docking of all selected virtual compounds in the library. FlexX is based on breaking ligands into fragments at rotatable bonds and then building them up again fragment by fragment and scoring the solutions. The output was limited to a maximum of top 10 poses per ligand; subsequently, we computed a free binding energy assessment (ΔG) in kcal/mol of the protein–ligand complex and its ligand efficiency using Hyde. , …”
Section: Methodsmentioning
confidence: 99%
“…The FlexX docking algorithm as implemented in LeadIT executed the docking of all selected virtual compounds in the library. FlexX is based on breaking ligands into fragments at rotatable bonds and then building them up again fragment by fragment and scoring the solutions. The output was limited to a maximum of top 10 poses per ligand; subsequently, we computed a free binding energy assessment (ΔG) in kcal/mol of the protein–ligand complex and its ligand efficiency using Hyde. , …”
Section: Methodsmentioning
confidence: 99%
“…Some of these residues are found to be conserved among HPV6, HPV11, HPV16, and HPV18 zinc fingers. This demonstrates the possibility of the zinc finger domain to be a drug target [ 41 ].…”
Section: E6 Proteinmentioning
confidence: 99%
“…Moreover, a study showed that the EBV protein called latent infection membrane protein 1 (LMP1) can act as a constitutively active receptor that mimics activated CD40, which is a member of the tumor necrosis factor receptor family (Mosialos et al 1995). Also there is another research indicated the E6 oncoprotein of HPV16 has a potential zinc finger domain critical for binding to E6AP ubiquitin-protein ligase which is an enzyme involved in targeting proteins for degradation within human cells, causing p53 degradation and malignancy (Choudhury et al 2014).…”
Section: Introductionmentioning
confidence: 99%